Anti-platelet Therapy Is Associated With Lower Risk of Dementia in Patients With Cerebral Small Vessel Disease - Pan, Dong; Rong, Xiaoming; Li, Honghong; Deng, Zhenhong; Wang, Jia; Liu, Xiaohuan; He, Lei; Xu, Yongteng; Tang, Yamei (Frontiers in Aging Neuroscience, 2022)
Introduction Cerebral small vessel disease (CSVD) is common among older people and it could lead to dementia. Whether anti-platelet therapy could retard cognitive decline of CSVD is unclear. The aim of the study was to evaluate, in newly diagnosed CSVD patients without dementia, the association between the anti-platelet therapy and dementia during follow-up. Methods We conducted a nested case-control study within a CSVD cohort. Dementia cases, including vascular dementia, Alzheimer’s disease and unspecified dementia, were individually matched (1:1) to controls by age, sex and follow-up time. Conditional logistic regression models were used to estimate odds ratios between anti-platelet therapy and dementia. Results Of 9,991 patients in cohort screened from January 2009 through December 2019 and followed up until November 2020, 131 dementia cases were finally included and successfully matched to 131 controls. Among 262 CSVD patients, the mean (SD) age was 73.9 (7.9) years, 126 (48.1%) were males. The median (IQR) follow-up periods were 4.73 (2.70-6.57) years in the control group and 2.94 (1.34-4.89) years in the case group. According to MRI at baseline, the case group showed higher CSVD burden in lacune(s) (P=0.001), moderate-to-severe white matter hyperintensities (P=0.015), enlarged perivascular spaces in basal ganglia (P=0.005), and brain atrophy(P<0.001). The anti-platelet therapy was associated with lower overall dementia risk and the matched odds ratio was statistically significant (aOR 0.15, 95%CI 0.05 to 0.45, P=0.001), and clopidogrel showed protective effects on overall dementia (aOR 0.30, 95%CI 0.14 to 0.62, P=0.001). Conclusions Among newly diagnosed CSVD patients without dementia, anti-platelet therapy was associated with a lower risk of dementia and clopidogrel might be an appropriate candidate in preventing dementia.